2014
DOI: 10.1093/humrep/deu297
|View full text |Cite
|
Sign up to set email alerts
|

Risk for borderline ovarian tumours after exposure to fertility drugs: results of a population-based cohort study

Abstract: No conflict of interest was reported. S.M.B. was supported by a research scholarship from the Danish Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 31 publications
2
43
2
Order By: Relevance
“…Specific subgroups of women did appear to be at higher risk for subsequent ovarian cancer. These subgroups included women with unexplained infertility, parous women with only one delivery as opposed to multiple deliveries following reproductive technology, women with PCOS, and women who had used progesterone therapy as part of their fertility treatment [8,10,15,19]. In a meta-analysis of 21 studies by Kvaskoff et al, 20 studies showed an elevated ovarian cancer risk in women with endometriosis, while one study failed to show this association [16].…”
Section: Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Specific subgroups of women did appear to be at higher risk for subsequent ovarian cancer. These subgroups included women with unexplained infertility, parous women with only one delivery as opposed to multiple deliveries following reproductive technology, women with PCOS, and women who had used progesterone therapy as part of their fertility treatment [8,10,15,19]. In a meta-analysis of 21 studies by Kvaskoff et al, 20 studies showed an elevated ovarian cancer risk in women with endometriosis, while one study failed to show this association [16].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…An analysis of publications shows that women with infertility had higher rates of psychiatric disorders and endometrial cancer than the general population [1][2][3][4][5][6][7][8][9][10]. Data is conflicting about whether infertile women are at increased risk for breast cancer and ovarian cancer [7,8,[10][11][12][13][14][15][16][17][18][19][20]. A generalized diagnosis of infertility was not clearly associated with an increased risk of cardiovascular disease or metabolic dysfunction, but women with infertility related to polycystic ovarian syndrome (PCOS) do appear more likely to develop cardioCapsule There is a growing body of literature addressing the impact of female infertility on long-term health.…”
mentioning
confidence: 99%
“…A recent case-cohort study of 96,545 Dutch subfertile women, including 142 cases of borderline ovarian tumors, found no association between all subtypes of ovarian borderline cancer and fertility medication use (RR: 1.00, 95% CI 0.67–1.51), which was consistent across fertility treatment cycles and follow-up duration [27]. An increased association between serous borderline ovarian tumors and progesterone use currently lacks biologic explanation.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Conversely, not all evidence demonstrates an association between fertility treatment and borderline ovarian tumors [27] [11] [28]. A recent case-cohort study of 96,545 Dutch subfertile women, including 142 cases of borderline ovarian tumors, found no association between all subtypes of ovarian borderline cancer and fertility medication use (RR: 1.00, 95% CI 0.67–1.51), which was consistent across fertility treatment cycles and follow-up duration [27].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Finally, a very recent study by Bjørnholt et al [48] analyzed data from a cohort of 96'545 women with fertility problems from all Danish fertility clinics during the years 1963-2006. They found that the overall risk for borderline ovarian tumors was not associated with the use of clomiphene citrate (RR 0.96; 95% CI 0.64-1.44).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%